PYRIMIDINE INCORPORATED SCHIFF BASE OF ISONIAZID WITH THEIR SYNTHESIS, CHARACTERIZATION AND IN VITRO BIOLOGICAL EVALUATION - Soni, Hetal I; Patel, Navin B (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Versatile biological activities of nitrogen containing heterocycles in medicinal chemistry, mainly pyrimidine and pyridine ring based heterocyclic moieties are very important. Pharmaceutical important of pyrimidine and isoniazid moiety prompted us to synthesize isoniazid clubbed pyrimidine derivatives and evaluated for antimicrobial and antituberculosis activity. Method: 2-(2-(3-bromo benzylidene)-1-isonicotinoyl hydrazinyl)-N-(4-(substituted phenyl)-6-(substituted aryl) pyrimidin-2-yl) acetamide 2(A-J) have been synthesized by condensation reaction of 2-chloro-N-[4-(substituted phenyl)-6-(substituted aryl) pyrimidin-2-yl] acetamide and N'-[(E)- (3-bromophenyl) methylidene]pyridine-4-carbohydrazide. All newly synthesized compounds were screened for in vitro antibacterial activity against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Staphylococcus pyogenes, antifungal against Candida albicans, Aspergillus niger, and Aspergillus clavatus, and antituberculosis activity against Mycobacterium tuberculosis H37RV. Results: Majority of the compounds exhibited good antibacterial, antifungal, and antituberculosis activity. All titled compounds were characterized by spectral analyses (infrared spectroscopy, nuclear magnetic resonance spectroscopy, and mass spectroscopy). Conclusion: 2-(2-(3-bromo benzylidene)-1-isonicotinoyl hydrazinyl)-N-(4-(substituted phenyl)-6-(substituted aryl) pyrimidin-2-yl) acetamide 2(A-J) showed good antimicrobial activity and comparatively good antituberculosis activity. Hence, all the compounds of this series considered for future investigation mainly in area of antibacterial, antifungal study.